A fast-curing silicone structural adhesive and preparation method thereof
By using microsphere reinforcement fillers, diatomaceous earth-sea carbon black composite, calcined diatomaceous earth and micro-nanowhiskers and other fillers with base glue, the problems of slow curing speed and bubble generation of single-component silicone structural glue are solved, and efficient curing and excellent bonding performance are achieved.
Patent Information
- Application Number
- CN202411226026.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-09-03
AI Technical Summary
The single-component silicone structural glue cures slowly under low temperature and low humidity conditions, and bubbles may occur under high temperature and high humidity conditions, affecting the surface flatness and bonding strength of the cured structural glue.
Microsphere reinforcement filler, diatomaceous earth-silver black composite, calcined diatomaceous earth and micro-nanowhiskers are used as fillers, and combined with base glue, plasticizer, crosslinking agent, coupling agent and defoaming agent to improve the curing speed and bonding strength of silicone structural glue, while reducing bubble generation.
The curing speed and bonding strength of silicone structural adhesive are significantly improved, the surface flatness and aesthetics after curing are improved, and the bonding strength with the substrate is enhanced.
Smart Images

Figure BDA0005024577620000151 
Figure BDA0005024577620000171 
Figure BDA0005024577620000181
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of adhesives, and more specifically, to a fast-curing silicone structural adhesive and a preparation method thereof. Background Art
[0002] Structural adhesive is a high-strength adhesive that can withstand large loads. It is mainly used in the fields of construction, engineering and industry to achieve bonding, anchoring and repairing of structural parts. According to the base adhesive composition of structural adhesive, it usually includes epoxy resin structural adhesive, polyurethane structural adhesive, acrylate structural adhesive, silicone structural adhesive, etc.
[0003] Among them, silicone structural adhesive uses silicone as the base adhesive, which has the advantages of strong adhesion, good aging resistance and stability, and high modulus after curing. It can be used for bonding metal, glass and other structural parts. Silicone structural adhesive generally includes single-component silicone structural adhesive and two-component silicone structural adhesive. Among them, single-component silicone structural adhesive is to pre-mix the raw materials first. When used, it relies on the reaction of the colloid with moisture in the air to perform curing and cross-linking. It has the advantages of simple operation and convenient use, but its curing time and curing speed are greatly affected by the ambient temperature and humidity. The curing speed is slow under low temperature and low humidity conditions, and it generally takes 5-15 days to fully cure. Under high temperature and high humidity conditions, bubbles may be generated, which will not only affect the surface flatness and aesthetics of the cured structural adhesive, but also reduce the contact area between the structural adhesive and the substrate, thereby reducing its bonding strength. Summary of the invention
[0004] In order to solve the above technical problems, the present application provides a fast curing silicone structural adhesive and a preparation method thereof.
[0005] In a first aspect, the present application provides a fast-curing silicone structural adhesive, which adopts the following technical solution:
[0006] A fast-curing silicone structural adhesive comprises the following raw materials in percentage by mass:
[0007] 30-80wt% of base rubber, 10-62wt% of filler, 4-8wt% of plasticizer, 3-6wt% of cross-linking agent, 0.5-2wt% of coupling agent, 0.03-2wt% of catalyst and 0.1-0.5wt% of defoaming agent;
[0008] The filler comprises a microspherical reinforcing filler, a diatomaceous earth-white carbon black composite, calcined diatomaceous earth and micro-nano whiskers in a weight ratio of 4-6:4-6:3-5:1;
[0009] Mix diatomaceous earth and magnesium oxide in a weight ratio of 3-5:1 to obtain a premix;
[0010] The premix is calcined at a temperature of 650-700° C. for 3-5 hours to obtain the calcined diatomaceous earth.
[0011] One-component silicone adhesive is cured by absorbing moisture from the air. Therefore, in order to increase the curing speed of silicone adhesive, it is necessary to increase the absorption rate of moisture by the one-component silicone adhesive. At the same time, it is also necessary to avoid the problem of bubbles caused by water absorption. In this embodiment, the filler includes microspherical reinforcing filler, diatomaceous earth-white carbon black composite, calcined diatomaceous earth and micro-nano whiskers; wherein, the diatomaceous earth-white carbon black composite, by utilizing the porosity of diatomaceous earth and white carbon black, can quickly absorb moisture from the air to increase the crosslinking reaction speed of the base adhesive and the crosslinking agent; on the other hand, by utilizing its large specific surface area, it can provide more reaction sites to accelerate the curing reaction.
[0012] Calcined diatomite is diatomite that has been calcined to remove impurities and organic matter in the diatomite to improve its purity; and the calcination treatment can improve the pore structure of the diatomite to increase its specific surface area and porosity, so as to facilitate its loading of crosslinking agents, catalysts, defoaming agents, etc., to further increase the curing reaction rate.
[0013] In addition, by adding defoaming agents to the raw materials, the bubbles generated by the silicone structural adhesive during water absorption and curing can be reduced; at the same time, through the synergistic effect of white carbon black, microspherical reinforcing fillers and micro-nano whiskers, the bubble discharge can be promoted and the bubbles can be caused to burst, thereby improving the leveling properties of the silicone structural adhesive, thereby improving the surface flatness and aesthetics of the silicone structural adhesive, and improving the bonding strength between the silicone structural adhesive and the substrate.
[0014] Ordinary diatomite ore has more impurities, which not only affect its hygroscopicity and load capacity, but also introduce too many impurities into the silicone structural adhesive, which leads to a decrease in the mechanical properties of the silicone structural adhesive; therefore, in this embodiment, the purity of the diatomite can be improved by calcining the diatomite; however, under high temperature conditions, the porous structure of the diatomite is easily destroyed, resulting in a smaller pore volume and larger pore size after calcination, thereby affecting the hygroscopicity of the diatomite; therefore, in this embodiment, magnesium oxide with better thermal stability and diatomite are calcined together, which not only helps to form a more uniform pore structure, but also can increase the specific surface area and mechanical strength of the calcined diatomite, so as to increase its load on cross-linking agents, catalysts, coupling agents, etc., so as to further increase the curing reaction rate.
[0015] In some embodiments, the diatomaceous earth-white carbon black composite is prepared by the following method:
[0016] The calcined diatomaceous earth is mixed with an aqueous solution of sodium hydroxide, and stirred at a temperature of 70-80° C. for 30-50 minutes to generate a mixed slurry containing sodium silicate;
[0017] Adding acid solution to the mixed slurry to convert sodium silicate into white carbon black, so as to obtain a diatomite-white carbon black intermediate;
[0018] The diatomite-white carbon black intermediate is aged, filtered and dried to obtain the diatomite-white carbon black composite.
[0019] In this embodiment, diatomite is loaded with white carbon black by using an alkali dissolution-acid precipitation method, which can improve the dispersibility and compatibility of diatomite in the base adhesive, and improve the mechanical strength of the silicone structural adhesive to achieve bonding, anchoring, and repairing of structural parts. Among them, in this embodiment, calcined diatomite is used as a silicon source, which can improve the activity, purity, and porosity of diatomite, increase the loading rate of diatomite on white carbon black, and improve the hygroscopicity of diatomite.
[0020] In some embodiments, the weight ratio of the calcined diatomaceous earth to the aqueous solution of sodium hydroxide is 1:6-8, and the concentration of the aqueous solution of sodium hydroxide is 5-8wt%;
[0021] The acid solution includes a sulfuric acid solution, the mass fraction of the sulfuric acid solution is 44-48wt%, and the volume ratio of the mixed slurry to the sulfuric acid solution is 3-5:1;
[0022] The aging temperature is 20-30° C., and the aging time is 4-6 hours.
[0023] In this embodiment, since calcined diatomite is used as the silicon source, compared with ordinary diatomite, the calcined diatomite in this embodiment has the characteristics of high purity, good activity, small pores, large specific surface area and porosity. Therefore, during alkali dissolution, a low concentration and content of sodium hydroxide aqueous solution can be used to generate sodium silicate on the surface of diatomite; and then a low mass fraction of sulfuric acid solution is used for acid precipitation to avoid damage to the microporous structure of diatomite. Then, after aging treatment at room temperature, the loading stability of diatomite on white carbon black can be improved.
[0024] In some embodiments, the microspherical reinforcing filler comprises calcium carbonate micropowder and talc powder in a weight ratio of 4-6:1;
[0025] The particle size of the calcium carbonate powder is 10-20 μm;
[0026] The particle size of the talc is 5-10 μm;
[0027] The micro-nano whiskers include calcium carbonate whiskers, and the length of the calcium carbonate whiskers is 20-30 μm and the diameter is 0.5-1.2 μm.
[0028] Calcium carbonate powder and calcium carbonate whisker can improve the strength, wear resistance and heat resistance of silicone structural adhesive, and their low price can reduce production costs; talcum powder can improve the fluidity of silicone structural adhesive and increase the drying speed of silicone structural adhesive; through the combination of microspherical calcium carbonate powder and talcum powder and fibrous calcium carbonate whisker, the mechanical strength of silicone structural adhesive can be improved while improving its fluidity, reducing the generation of bubbles, promoting the discharge of bubbles and causing them to burst, improving the leveling of silicone structural adhesive, thereby improving the surface smoothness and aesthetics of silicone structural adhesive and improving the bonding strength between silicone structural adhesive and substrate.
[0029] In some embodiments, the gum base includes hydroxy-terminated polydimethylsiloxane;
[0030] The plasticizer includes a combination of one or more of methyl silicone oil and liquid paraffin;
[0031] The crosslinking agent includes a combination of one or more of methyltrimethoxysilane, dimethyldimethoxysilane, vinyltrimethoxysilane, propyltrimethoxysilane, methyltriisobutylketoxime silane, and vinyltriisobutylketoxime silane;
[0032] The coupling agent includes a combination of one or more of an amino silane coupling agent, a methacrylic silane coupling agent, a mercapto silane coupling agent, and an ethoxy silane coupling agent;
[0033] The catalyst includes a combination of one or more of an organic tin catalyst and a titanate catalyst;
[0034] The defoamer includes a combination of one or more of an organosilicon defoamer, a polyether-modified organosilicon defoamer, and a silicon-free polymer defoamer.
[0035] In this embodiment, the base glue includes terminal hydroxyl polydimethylsiloxane, which has good mechanical properties, chemical resistance and thermal stability; illustratively, the terminal hydroxyl polydimethylsiloxane can be selected from α, ω-dihydroxy polydimethylsiloxane, such as WS-62M, BSM207, DY-OH502N, etc.
[0036] The plasticizer may be methyl silicone oil, liquid paraffin or a combination of the two, wherein the methyl silicone oil may be, for example, dimethyl silicone oil MSD-201.
[0037] The crosslinking agent can be selected from a combination of one or more of methyltrimethoxysilane, dimethyldimethoxysilane, vinyltrimethoxysilane, propyltrimethoxysilane, methyltriisobutylketoneoximesilane, and vinyltriisobutylketoneoximesilane; for example, the crosslinking agent can be selected from methyltrimethoxysilane, or the crosslinking agent is a combination of methyltrimethoxysilane and methyltriisobutylketoneoximesilane in a weight ratio of 1:1.
[0038] The coupling agent can be selected from a combination of one or more of an amino silane coupling agent, a methacrylate silane coupling agent, a mercapto silane coupling agent, and an ethoxy silane coupling agent; wherein the amino silane coupling agent may be, for example, γ-aminopropylmethyldiethoxysilane (Si-902) or 3-aminopropyltrimethoxysilane (APS); the methacrylate silane coupling agent may be, for example, 3-(methacryloyloxy)propyltrimethoxysilane; the mercapto silane coupling agent may be, for example, γ-mercaptopropyltriethoxysilane; and the ethoxy silane coupling agent may be, for example, an ethoxy silane coupling agent. Exemplarily, the coupling agent is a composition of γ-aminopropylmethyldiethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane and γ-mercaptopropyltriethoxysilane in a weight ratio of 2:1:1. Compared with a single coupling agent, the compound use of multiple coupling agents can not only improve the dispersibility and compatibility of the filler and the base glue, improve the curing depth and curing efficiency of the silicone structural adhesive, but also improve the bonding strength between the silicone structural adhesive and different substrates, so as to improve the wide application of the silicone structural adhesive.
[0039] The catalyst may be a combination of one or more of an organic tin catalyst and a titanate catalyst, wherein the organic tin catalyst may be, for example, stannous octoate, dibutyltin diacetate, dibutyltin dilaurate; the titanate catalyst may be, for example, tetra-n-butyl titanate.
[0040] The defoamer may be a combination of one or more of a silicone defoamer and a polyether-modified silicone defoamer; wherein the silicone defoamer may be, for example, AFE-3168 or PX-122; the polyether-modified silicone defoamer may be, for example, Tego Foamex 825; and the silicone-free polymer defoamer may be, for example, BYK-054.
[0041] In a second aspect, the present application provides a method for preparing a fast-curing silicone structural adhesive, using the following technical solution:
[0042] A method for preparing a fast-curing silicone structural adhesive comprises the following steps:
[0043] S1, mixing the calcined diatomaceous earth with the cross-linking agent and the coupling agent to obtain a first mixture;
[0044] S2, mixing the base glue with the microspherical reinforcing filler, the diatomaceous earth-white carbon black composite and the micro-nano whiskers to obtain a second mixture;
[0045] S3, mixing the first mixture, the second mixture, the plasticizer, the catalyst and the defoamer to obtain the fast-curing silicone structural adhesive.
[0046] In some embodiments, step S1 includes:
[0047] S11, adding the coupling agent and the cross-linking agent into an anhydrous organic solvent, mixing them evenly to obtain a premixed solution;
[0048] S12, mixing the premixed liquid with the calcined diatomaceous earth, and stirring for 2-4 hours under vacuum to obtain a mixture;
[0049] S13, filtering the mixture to remove the anhydrous organic solvent to obtain a precipitate;
[0050] S14, drying the precipitate to obtain the first mixture.
[0051] In this embodiment, the calcined diatomite is premixed with the coupling agent and the crosslinking agent, and the calcined diatomite is loaded with the coupling agent and the crosslinking agent by an impregnation method, which can improve the dispersibility of the coupling agent and the crosslinking agent and thus increase the curing speed.
[0052] In some embodiments, the anhydrous organic solvent includes one of anhydrous ethanol and anhydrous acetone;
[0053] In the step S12, the vacuum is evacuated to -0.08 to -0.095 MPa, the stirring speed is 400-500 rpm, and the stirring time is 2-4 hours.
[0054] In some embodiments, in step S2, the stirring temperature is 120-130°C, the stirring speed is 400-600rpm, the stirring time is 60-90min, the vacuum is evacuated to -0.08 to -0.095MPa, and the dehydration time is 1-2h;
[0055] In the step S3, the stirring temperature is 110-115° C., the stirring speed is 800-1000 rpm, the stirring time is 30-60 min, the vacuum is drawn to -0.08 to -0.095 MPa, and the dehydration time is 1-2 h.
[0056] In summary, this application has the following beneficial effects:
[0057] 1. The present application uses microspherical reinforcing fillers, diatomaceous earth-white carbon black composites, calcined diatomaceous earth and micro-nano whiskers as fillers, and combines them with base glue, plasticizer, cross-linking agent, coupling agent and defoaming agent to improve the bonding strength of silicone structural adhesive, increase the curing speed of silicone structural adhesive, and reduce the generation of bubbles, thereby improving the surface smoothness and aesthetics of the cured silicone structural adhesive.
[0058] 2. The microspherical reinforcing filler in the filler of the present application can play a reinforcing role to improve the mechanical properties of the structural adhesive; the specific porosity and large specific surface area of the diatomaceous earth-white carbon black composite can increase the crosslinking reaction rate between the base adhesive and the crosslinking agent and accelerate the curing reaction; the calcined diatomaceous earth is diatomaceous earth that has been calcined to improve its pore structure; through the synergistic combination of microspherical reinforcing fillers, diatomaceous earth-white carbon black composites, and calcined diatomaceous earth, the curing rate can be increased while the mechanical strength of the structural adhesive is increased.
[0059] 3. The present application can reduce the bubbles generated during water absorption and curing of the silicone structural adhesive and promote the discharge of bubbles and cause the bubbles to burst through the synergistic combination of the defoaming agent and the white carbon black, microspherical reinforcing filler and micro-nano whiskers in the filler; wherein, by combining microspherical calcium carbonate powder and talcum powder and fibrous calcium carbonate whiskers, the mechanical strength of the silicone structural adhesive can be improved while its fluidity is improved, the generation of bubbles can be reduced, the discharge of bubbles can be promoted and the bubbles can be caused to burst, and the leveling property of the silicone structural adhesive can be improved, thereby improving the surface smoothness and aesthetics of the silicone structural adhesive and improving the bonding strength between the silicone structural adhesive and the substrate.
[0060] 4. In the preparation of calcined diatomite, the present application calcines magnesium oxide and diatomite with good thermal stability together, which not only helps to form a more uniform pore structure, but also can improve the specific surface area and mechanical strength of the calcined diatomite; when the calcined diatomite is used to prepare a diatomite-white carbon black composite, the uniformity of its white carbon black loading can be improved; and when preparing silicone structural adhesives, the calcined diatomite can be used to load coupling agents and cross-linking agents, which can improve the dispersibility of the coupling agents and cross-linking agents to increase the curing speed. DETAILED DESCRIPTION
[0061] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be arbitrarily combined with each other.
[0062] Preparation Example of Calcined Diatomaceous Earth
[0063] It should be noted that, unless otherwise specified, the raw materials in the following preparation examples can be obtained from commercial sources. Among them, diatomaceous earth is ordinary diatomaceous earth with a fineness of 400 meshes; magnesium oxide is magnesium oxide powder with a fineness of 600 meshes.
[0064] Preparation Example 1 of calcined diatomite:
[0065] Mix diatomaceous earth and magnesium oxide in a weight ratio of 3:1 to obtain a premix;
[0066] The premix was calcined at 650° C. for 5 h to obtain calcined diatomaceous earth.
[0067] Preparation Example 2 of calcined diatomite:
[0068] Mix diatomaceous earth and magnesium oxide in a weight ratio of 4:1 to obtain a premix;
[0069] The premix was calcined at 680° C. for 4 h to obtain calcined diatomaceous earth.
[0070] Preparation Example 3 of calcined diatomite:
[0071] Mix diatomaceous earth and magnesium oxide in a weight ratio of 5:1 to obtain a premix;
[0072] The premix was calcined at 700° C. for 3 h to obtain calcined diatomaceous earth.
[0073] Preparation Example 4 of calcined diatomite: calcined diatomite at 650° C. for 5 h to obtain calcined diatomite.
[0074] Preparation example of diatomite-white carbon black composite
[0075] It should be noted that, unless otherwise specified, the raw materials in the following preparation examples can be obtained from commercial sources.
[0076] Preparation Example 1 of Diatomaceous Earth-Silica Carbon Black Composite:
[0077] ① Mix calcined diatomite and an aqueous solution of sodium hydroxide, and stir at a temperature of 70° C. for 50 min to generate a mixed slurry containing sodium silicate; wherein the calcined diatomite is prepared by Preparation Example 1 of calcined diatomite; the weight ratio of the calcined diatomite to the aqueous solution of sodium hydroxide is 1:6, and the concentration of the aqueous solution of sodium hydroxide is 8wt%;
[0078] ② Adding a sulfuric acid solution with a mass fraction of 44wt% to the mixed slurry to generate white carbon black from sodium silicate to obtain a diatomite-white carbon black intermediate; wherein the volume ratio of the mixed slurry to the sulfuric acid solution is 3:1;
[0079] ③ The diatomite-white carbon black intermediate is aged, filtered and dried to obtain a diatomite-white carbon black composite; wherein the aging temperature is 20° C., the aging time is 6 h; the drying temperature is 120° C., and the drying time is 6 h.
[0080] Preparation Example 2 of Diatomaceous Earth-Silica Carbon Black Composite:
[0081] ① Mixing calcined diatomite with an aqueous solution of sodium hydroxide, stirring at a temperature of 75° C. for 40 min to generate a mixed slurry containing sodium silicate; wherein the calcined diatomite is prepared by Preparation Example 1 of calcined diatomite; the weight ratio of the calcined diatomite to the aqueous solution of sodium hydroxide is 1:7, and the concentration of the aqueous solution of sodium hydroxide is 7wt%;
[0082] ② Adding a sulfuric acid solution with a mass fraction of 46wt% to the mixed slurry to generate white carbon black from sodium silicate to obtain a diatomite-white carbon black intermediate; wherein the volume ratio of the mixed slurry to the sulfuric acid solution is 4:1;
[0083] ③ The diatomite-white carbon black intermediate is aged, filtered and dried to obtain a diatomite-white carbon black composite; wherein the aging temperature is 25° C., the aging time is 5 h; the drying temperature is 120° C., and the drying time is 6 h.
[0084] Preparation Example 3 of Diatomaceous Earth-White Carbon Black Composite:
[0085] ① Mixing calcined diatomite with an aqueous solution of sodium hydroxide, stirring at a temperature of 80° C. for 30 min to generate a mixed slurry containing sodium silicate; wherein the calcined diatomite is prepared by Preparation Example 1 of calcined diatomite; the weight ratio of the calcined diatomite to the aqueous solution of sodium hydroxide is 1:8, and the concentration of the aqueous solution of sodium hydroxide is 5wt%;
[0086] ② Adding a sulfuric acid solution with a mass fraction of 48wt% to the mixed slurry to generate white carbon black from sodium silicate to obtain a diatomite-white carbon black intermediate; wherein the volume ratio of the mixed slurry to the sulfuric acid solution is 5:1;
[0087] ③ The diatomite-white carbon black intermediate is aged, filtered and dried to obtain a diatomite-white carbon black composite; wherein the aging temperature is 30° C., the aging time is 4 h; the drying temperature is 120° C., and the drying time is 6 h.
[0088] Preparation Example 4 of Diatomaceous Earth-Silica Composite: The main difference between this Preparation Example and Preparation Example 2 is that the calcined diatomaceous earth is replaced by an equal amount of common diatomaceous earth with a fineness of 400 meshes.
[0089] Preparation Example 5 of Diatomaceous Earth-White Carbon Black Composite: Calcined Diatomaceous Earth was prepared according to Preparation Example 4 of calcined diatomaceous earth.
[0090] Example
[0091] It should be noted that, unless otherwise specified, the raw materials in the following examples can be obtained from commercial sources.
[0092] Among them, the base rubber is α,ω-dihydroxypolydimethylsiloxane; the particle size of the calcium carbonate micropowder in the filler is 10-20μm; the particle size of the talc powder is 5-10μm; the micro-nano whiskers are calcium carbonate whiskers, the length of the calcium carbonate whiskers is 20-30μm, and the diameter is 0.5-1.2μm; the plasticizer is dimethyl silicone oil; the cross-linking agent is a composition of methyltrimethoxysilane and methyltriisobutylketoximesilane in a weight ratio of 1:1; the coupling agent is a composition of γ-aminopropylmethyldiethoxysilane, 3-(methacryloyloxy)propyltrimethoxysilane and γ-mercaptopropyltriethoxysilane in a weight ratio of 2:1:1; the catalyst is dibutyltin diacetate; and the defoaming agent is a silicone defoaming agent.
[0093] Embodiment 1: A method for preparing a fast-curing silicone structural adhesive, comprising the following steps:
[0094] (1) Add a coupling agent and a cross-linking agent to anhydrous ethanol and mix them evenly to obtain a premixed solution; after mixing the premixed solution with calcined diatomaceous earth, evacuate to -0.08 MPa, and stir at a stirring speed of 400 rpm for 4 hours to obtain a mixture; filter the mixture to remove anhydrous ethanol to obtain a precipitate; heat the precipitate to 120° C., maintain for 5 hours, and dry to obtain a first mixture.
[0095] (2) The base rubber, microspherical reinforcing filler, diatomaceous earth-white carbon black composite and micro-nano whiskers were stirred at a temperature of 120° C. and a stirring speed of 400 rpm for 90 min to mix them evenly, and then vacuum-dehydrated at -0.08 MPa for 2 h to obtain a second mixture.
[0096] (3) The first mixture, the second mixture, the plasticizer, the catalyst and the defoaming agent were stirred at a temperature of 110° C. and a stirring speed of 800 rpm for 60 min to mix them evenly, and then vacuum-dried at -0.08 MPa for 2 h to obtain a fast-curing silicone structural adhesive.
[0097] Wherein, the mass percentage of each raw material in this embodiment is as follows:
[0098] 30wt% of base rubber, 62wt% of filler, 4wt% of plasticizer, 3wt% of cross-linking agent, 0.87wt% of coupling agent, 0.03wt% of catalyst and 0.1wt% of defoaming agent.
[0099] The filler includes a microspherical reinforcing filler, a diatomaceous earth-white carbon black composite, calcined diatomaceous earth and micro-nano whiskers in a weight ratio of 4:4:3:1; the microspherical reinforcing filler includes calcium carbonate powder and talcum powder in a weight ratio of 4:1; the diatomaceous earth-white carbon black composite is prepared by Preparation Example 1 of the diatomaceous earth-white carbon black composite, and the calcined diatomaceous earth is prepared by Preparation Example 1 of the calcined diatomaceous earth.
[0100] Embodiment 2: A method for preparing a fast-curing silicone structural adhesive, comprising the following steps:
[0101] (1) Add a coupling agent and a cross-linking agent to anhydrous ethanol and mix them evenly to obtain a premixed solution; after mixing the premixed solution with calcined diatomaceous earth, evacuate to -0.09 MPa, and stir at a stirring speed of 500 rpm for 3 hours to obtain a mixture; filter the mixture to remove the anhydrous ethanol to obtain a precipitate; heat the precipitate to 125° C., maintain for 5 hours, and dry to obtain a first mixture.
[0102] (2) The base rubber, microspherical reinforcing filler, diatomaceous earth-white carbon black composite and micro-nano whiskers were stirred at a temperature of 125° C. and a stirring speed of 500 rpm for 75 minutes to mix them evenly, and then vacuum-dehydrated at -0.09 MPa for 1.5 hours to obtain a second mixture.
[0103] (3) The first mixture, the second mixture, the plasticizer, the catalyst and the defoaming agent were stirred at a temperature of 112° C. and a stirring speed of 900 rpm for 45 minutes to mix them evenly, and then vacuumed at -0.095 MPa for dehydration for 1.5 hours to obtain a fast-curing silicone structural adhesive.
[0104] Wherein, the mass percentage of each raw material in this embodiment is as follows:
[0105] 57.7wt% of base rubber, 24wt% of filler, 8wt% of plasticizer, 6wt% of cross-linking agent, 2wt% of coupling agent, 2wt% of catalyst and 0.3wt% of defoaming agent.
[0106] The filler includes a microspherical reinforcing filler, a diatomaceous earth-white carbon black composite, calcined diatomaceous earth and micro-nano whiskers in a weight ratio of 5:5:4:1; the microspherical reinforcing filler includes calcium carbonate powder and talcum powder in a weight ratio of 5:1; the diatomaceous earth-white carbon black composite is prepared by Preparation Example 2 of the diatomaceous earth-white carbon black composite, and the calcined diatomaceous earth is prepared by Preparation Example 2 of the calcined diatomaceous earth.
[0107] Embodiment 3: A method for preparing a fast-curing silicone structural adhesive, comprising the following steps:
[0108] (1) Add a coupling agent and a cross-linking agent to anhydrous ethanol and mix them evenly to obtain a premixed solution; after mixing the premixed solution with calcined diatomaceous earth, evacuate to -0.095 MPa, and stir at a stirring speed of 400 rpm for 4 hours to obtain a mixture; filter the mixture to remove anhydrous ethanol to obtain a precipitate; heat the precipitate to 120° C., maintain for 5 hours, and dry to obtain a first mixture.
[0109] (2) The base rubber, microspherical reinforcing filler, diatomaceous earth-white carbon black composite and micro-nano whiskers were stirred at a temperature of 130° C. and a stirring speed of 600 rpm for 60 min to mix them evenly, and then vacuum-dehydrated at -0.095 MPa for 1 h to obtain a second mixture.
[0110] (3) The first mixture, the second mixture, the plasticizer, the catalyst and the defoaming agent were stirred at a temperature of 115° C. and a stirring speed of 1000 rpm for 30 minutes to mix them evenly, and then vacuum-dried at -0.095 MPa for 1 hour to obtain a fast-curing silicone structural adhesive.
[0111] Wherein, the mass percentage of each raw material in this embodiment is as follows:
[0112] 80wt% of base rubber, 10wt% of filler, 4wt% of plasticizer, 3wt% of cross-linking agent, 1.5wt% of coupling agent, 1wt% of catalyst and 0.5wt% of defoaming agent.
[0113] The filler includes a microspherical reinforcing filler, a diatomaceous earth-white carbon black composite, calcined diatomaceous earth and micro-nano whiskers in a weight ratio of 6:6:5:1; the microspherical reinforcing filler includes calcium carbonate powder and talcum powder in a weight ratio of 6:1; the diatomaceous earth-white carbon black composite is prepared by Preparation Example 3 of the diatomaceous earth-white carbon black composite, and the calcined diatomaceous earth is prepared by Preparation Example 3 of the calcined diatomaceous earth.
[0114] In order to more clearly explain the technical solution of the present application, the present application also lists Examples 4-6, wherein the formula of Examples 4-6 is shown in Table 1. It should be noted that, except for the formula of raw materials listed in Table 1, other parameters of Examples 4-6 and Example 1 are basically the same.
[0115] Table 1 Raw material dosage table of Examples 1-6 (unit: wt%)
[0116]
[0117] Example 7: The main difference between this example and Example 2 is that the diatomite-white carbon black composite is prepared by Preparation Example 4 of the diatomite-white carbon black composite.
[0118] Comparative Example
[0119] Comparative Example 1: A method for preparing a silicone structural adhesive, comprising the following steps:
[0120] (1) The base rubber and filler were stirred at a temperature of 125° C. and a stirring speed of 500 rpm for 75 minutes to mix them evenly, and then vacuum-dried at -0.09 MPa for 1.5 hours to obtain a first mixture.
[0121] (2) The first mixture, the crosslinking agent, the coupling agent, the catalyst, the plasticizer and the defoaming agent were stirred at a temperature of 112° C. and a stirring speed of 900 rpm for 45 minutes to mix them evenly, and then vacuum-dehydrated at -0.095 MPa for 1.5 hours to obtain a silicone structural adhesive.
[0122] Wherein, the mass percentage of each raw material in this comparative example is as follows:
[0123] 52.7wt% of base rubber, 29wt% of filler, 8wt% of plasticizer, 6wt% of cross-linking agent, 2wt% of coupling agent, 2wt% of catalyst and 0.3wt% of defoaming agent.
[0124] The base rubber is α,ω-dihydroxypolydimethylsiloxane; the filler is a composition of calcium carbonate powder and diatomaceous earth in a weight ratio of 1:1, the particle size of calcium carbonate is 10-20μm, and the fineness of diatomaceous earth is 400 mesh; the plasticizer is dimethyl silicone oil; the cross-linking agent is methyltrimethoxysilane; the coupling agent is γ-aminopropylmethyldiethoxysilane; the catalyst is dibutyltin diacetate; and the defoaming agent is a silicone defoaming agent.
[0125] Comparative Example 2: The main difference between this comparative example and Example 2 is that the calcined diatomaceous earth in the filler is replaced by an equal amount of base gum.
[0126] The preparation method of silicone structural adhesive comprises the following steps:
[0127] (1) The base rubber and filler were stirred at a temperature of 125° C. and a stirring speed of 500 rpm for 75 minutes to mix them evenly, and then vacuum-dried at -0.09 MPa for 1.5 hours to obtain a first mixture.
[0128] (2) The first mixture, the crosslinking agent, the coupling agent, the catalyst, the plasticizer and the defoaming agent were stirred at a temperature of 112° C. and a stirring speed of 900 rpm for 45 minutes to mix them evenly, and then vacuum-dehydrated at -0.095 MPa for 1.5 hours to obtain a silicone structural adhesive.
[0129] Comparative Example 3: The main difference between this comparative example and Example 2 is that the diatomaceous earth-white carbon black composite is replaced by an equal amount of base glue.
[0130] Comparative Example 4: The main difference between this comparative example and Example 2 is that the micro-nano whiskers are replaced with an equal amount of base glue.
[0131] Comparative Example 5: The main difference between this comparative example and Example 2 is that the diatomite-white carbon black composite is prepared by Preparation Example 5 of the diatomite-white carbon black composite, and the calcined diatomite is prepared by Preparation Example 4 of the calcined diatomite.
[0132] Performance Testing
[0133] Silicone structural adhesive was prepared according to the methods of the embodiment and the comparative example, and the performance of the silicone structural adhesive was tested according to the following method. The test conditions were (23±2)℃ / (50±2)%RH and (23±2)℃ / (35±2)%RH, respectively. The test results are recorded in Table 2.
[0134] 1. Surface drying time: refer to the method of GB / T16776-2005 "Silicone structural sealant for construction" to measure the surface drying time.
[0135] 2. Curing rate: Determine the curing rate according to the curing rate test method in GB / T 29595-2013 “Silicone rubber sealant for terrestrial photovoltaic module sealing materials”.
[0136] 3. Tensile bond strength: refer to the method of GB / T16776-2005 "Silicone structural sealant for construction" to measure the tensile bond.
[0137] 4. Appearance: Cure the silicone structural adhesive under the set temperature and humidity environment for 48 hours, and observe the flatness of the adhesive surface and whether there are pinholes, shrinkage and other appearance defects; the adhesive surface that is flat and smooth without obvious pinholes, shrinkage and other appearance defects is recorded as A, and the adhesive surface that is rough or has obvious pinholes, shrinkage and other appearance defects is recorded as B.
[0138] Table 2 Performance test table of silicone structural adhesive of embodiment and comparative example
[0139]
[0140]
[0141] It can be seen from the data in Table 1 and Table 2 that the silicone structural adhesive prepared by the method of the embodiment of the present application has the advantages of fast curing speed, high bonding tensile strength and good surface flatness. It can be seen from Examples 1-6 that when the content of the base adhesive and the filler changes, it has a significant effect on the curing time, curing rate, bonding tensile strength and appearance of the silicone structural adhesive. It can be seen from Examples 2 and 7 that the addition of diatomaceous earth-white carbon black composite and calcined diatomaceous earth in the filler can increase the curing speed and improve the tensile bonding strength of the silicone structural adhesive.
[0142] It can be seen from the data in Table 2 that, compared with Example 2, the curing speed of the silicone structural adhesive in Comparative Example 2 is reduced, and the bonding strength is significantly reduced, indicating that the addition of calcined diatomaceous earth in the filler can increase the curing speed, and because it can improve the dispersion uniformity of the cross-linking agent and the coupling agent, it can increase the curing cross-linking depth, which helps to improve the viscosity strength of the silicone structural adhesive.
[0143] Compared with Example 2, the surface drying time of the silicone structural adhesive in Comparative Example 3 is increased and the curing speed is decreased. Especially in an environment with low humidity, the surface drying time, curing rate and bonding strength of the silicone structural adhesive are significantly reduced, indicating that the addition of diatomaceous earth-white carbon black composite in the filler can improve the curing speed and bonding strength of the silicone structural adhesive.
[0144] Compared with Example 2, the bonding strength of the silicone structural adhesive in Comparative Example 4 is reduced, and in an environment with high humidity, appearance defects such as pinholes and shrinkage will appear on the adhesive surface, indicating that the addition of micro-nano whiskers in the filler can improve the bubble problem caused by excessive water absorption of the silicone structural adhesive, thereby reducing the problem of decreased bonding strength of the silicone structural adhesive caused by bubbles.
[0145] In combination with Example 2 and Comparative Examples 2-4, it can be seen that the microspherical reinforcing filler, diatomaceous earth-white carbon black composite, calcined diatomaceous earth and micro-nano whiskers in the filler of the present application have a synergistic effect, which can improve the curing rate of the silicone structural adhesive while improving its fluidity, thereby improving the surface flatness and aesthetics of the silicone structural adhesive and improving the bonding strength between the silicone structural adhesive and the substrate.
[0146] Combining Example 2 and Comparative Example 5, it can be seen that the curing speed of the silicone structural adhesive in Comparative Example 2 is reduced and the bonding strength is significantly reduced, indicating that when preparing calcined diatomite, the addition of magnesium oxide can improve the pore structure of diatomite and increase its load on cross-linking agents and coupling agents, thereby improving the curing speed and depth, so as to improve the bonding strength of the curing speed structural adhesive.
[0147] In summary, the present application can effectively improve the curing speed, bonding strength and surface flatness of silicone structural adhesive by adjusting the formula of silicone structural adhesive, and is suitable for bonding, anchoring and repairing of structural parts.
[0148] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A fast-curing silicone structural adhesive, characterized in that: The raw materials include the following mass percentages: 30-80wt% of base rubber, 10-62wt% of filler, 4-8wt% of plasticizer, 3-6wt% of cross-linking agent, 0.5-2wt% of coupling agent, 0.03-2wt% of catalyst and 0.1-0.5wt% of defoaming agent; The filler comprises a microspherical reinforcing filler, a diatomaceous earth-white carbon black composite, calcined diatomaceous earth and micro-nano whiskers in a weight ratio of 4-6:4-6:3-5:1; The calcined diatomite is prepared by the following method: Mix diatomaceous earth and magnesium oxide in a weight ratio of 3-5:1 to obtain a premix; calcining the premix at a temperature of 650-700° C. for 3-5 hours to obtain the calcined diatomite; The microspherical reinforcing filler comprises calcium carbonate powder and talcum powder in a weight ratio of 4-6:1; The micro-nano whiskers include calcium carbonate whiskers; The diatomite-white carbon black composite is prepared by the following method: The calcined diatomaceous earth is mixed with an aqueous solution of sodium hydroxide, and stirred at a temperature of 70-80° C. for 30-50 minutes to generate a mixed slurry containing sodium silicate; Adding acid solution to the mixed slurry to convert sodium silicate into white carbon black, so as to obtain a diatomite-white carbon black intermediate; The diatomite-white carbon black intermediate is aged, filtered and dried to obtain the diatomite-white carbon black composite; The weight ratio of the calcined diatomaceous earth to the aqueous solution of sodium hydroxide is 1:6-8, and the concentration of the aqueous solution of sodium hydroxide is 5-8wt%; The acid solution includes a sulfuric acid solution, the mass fraction of the sulfuric acid solution is 44-48wt%, and the volume ratio of the mixed slurry to the sulfuric acid solution is 3-5:1; The gum base includes hydroxy-terminated polydimethylsiloxane.
2. The fast curing silicone structural adhesive according to claim 1, characterized in that: The aging temperature is 20-30° C., and the aging time is 4-6 hours.
3. The fast curing silicone structural adhesive according to claim 1, characterized in that: The particle size of the calcium carbonate powder is 10-20 μm; The particle size of the talc is 5-10 μm; The calcium carbonate whisker has a length of 20-30 μm and a diameter of 0.5-1.2 μm.
4. The fast curing silicone structural adhesive according to claim 1, characterized in that: The plasticizer includes a combination of one or more of methyl silicone oil and liquid paraffin; The crosslinking agent includes a combination of one or more of methyltrimethoxysilane, dimethyldimethoxysilane, vinyltrimethoxysilane, propyltrimethoxysilane, methyltriisobutylketoxime silane, and vinyltriisobutylketoxime silane; The coupling agent includes a combination of one or more of an amino silane coupling agent, a methacrylic silane coupling agent, and a mercapto silane coupling agent; The catalyst includes a combination of one or more of an organic tin catalyst and a titanate catalyst; The defoamer includes a combination of one or more of an organosilicon defoamer, a polyether-modified organosilicon defoamer, and a silicon-free polymer defoamer.
5. A method for preparing the fast-curing silicone structural adhesive as claimed in claim 1, characterized in that: The steps include: S1, mixing the calcined diatomaceous earth with the cross-linking agent and the coupling agent to obtain a first mixture; S2, mixing the base glue with the microspherical reinforcing filler, the diatomaceous earth-white carbon black composite and the micro-nano whiskers, and vacuuming and dehydrating to obtain a second mixture; S3, stirring and mixing the first mixture, the second mixture, the plasticizer, the catalyst and the defoamer to obtain the fast-curing silicone structural adhesive.
6. The method for preparing the fast-curing silicone structural adhesive according to claim 5, characterized in that: The step S1 comprises: S11, adding the coupling agent and the cross-linking agent into an anhydrous organic solvent, mixing them evenly to obtain a premixed solution; S12, mixing the premixed liquid with the calcined diatomaceous earth, and stirring under vacuum to obtain a mixture; S13, filtering the mixture to remove the anhydrous organic solvent to obtain a precipitate; S14, drying the precipitate to obtain the first mixture.
7. The method for preparing the fast-curing silicone structural adhesive according to claim 6, characterized in that: The anhydrous organic solvent includes one of anhydrous ethanol and anhydrous acetone; In the step S12, the vacuum is evacuated to -0.08 to -0.095 MPa, the stirring speed is 400-500 rpm, and the stirring time is 2-4 hours.
8. The method for preparing the fast-curing silicone structural adhesive according to claim 5, characterized in that: In step S2, the stirring temperature is 120-130°C, the stirring speed is 400-600rpm, the stirring time is 60-90min, the vacuum is evacuated to -0.08 to -0.095MPa, and the dehydration time is 1-2h; In the step S3, the stirring temperature is 110-115° C., the stirring speed is 800-1000 rpm, the stirring time is 30-60 min, and the process also includes evacuating to -0.08 to -0.095 MPa and dehydrating for 1-2 h.
Citation Information
Patent Citations
Humidity conditioning diatom ooze material and preparation method thereof
CN108892454A
Treatment method of phenol wastewater
CN111268758A
Damp and heat resistant silicone structural adhesive suitable for photovoltaic module
CN118006291A